SYSTEMATIC LITERATURE REVIEW EFEKTIFITAS PENGGUNAAN MICROSOFT TEAMS DALAM PEMBELAJARAN DARING - Noor, Apriadi; Nashar Utamajaya, Joy (Jurnal Rekayasa Perangkat Lunak dan Sistem Informasi, 2023)
During the last 2 years COVID-19 has changed human habits, adapting to new habits which are better known as New Normal. The government mandates PSSB that all teaching staff in public and private schools are required to work from home during the learning process. The transition from conventional to bold is influenced by this condition. One application that can be used for bold learning is Microsoft Teams. Microsoft Teams enables teachers and students to interact so that they feel like they are face to face. The purpose of this study is to identify the effectiveness of Microsoft Teams in learning to dare, using data from related journals from 2017 to 2020, how well literature studies are used as this research method. The review results obtained from 12 of the 13 journals that were reviewed or with a proportion of 92% stated that Microsoft Teams was effective in learning courage, using decision-making methods, namely the value of learning outcomes, questionnaires, observations, and interviews. Many features are offered by Microsoft Teams, such as its main feature, namely the Online Meeting (Video Conference) feature. Most of the obstacles that exist in Microsoft Teams are external constraints to the Microsoft Teams application itself, these obstacles occur in areas where the technology infrastructure and network are still inadequate.